Using corpora to track changing thought styles: evidentiality, epistemology, and Early Modern English and German scientific discourse - Whitt, Richard J. (Kalbotyra, 2017)
Most research on evidentiality has focused on classifying evidential systems synchronically; meanwhile, diachronic studies on evidentiality seem to have focused on the development of specific items into evidential markers with little regard to discourse context. This paper begins to fill this gap by presenting the results of a corpus-based study of evidential markers in Early Modern scientific discourse in English and German. The Early Modern period witnessed the transition from scholastic-based models of science to more empirical models of enquiry; this study demonstrates a decrease in the use of markers of mediated information and an increase in the use of markers of direct observation and inference accompanying these sociohistorical developments.
Keywords: Evidentiality; Early Modern Period; Scientific Discourse; English; German